TRANSFORMASI PELAYANAN KESEHATAN IBU DAN ANAK SERTA INTERVENSI GIZI: DAMPAKNYA TERHADAP PREVALENSI STUNTING DI INDONESIA - Rusyda, Akifa Laila; Baliwati, Yayuk Farida (Persagi, 2024)
Stunting in children under five is still a health problem in Indonesia. The study's objective was to evaluate the influence of essential nutrition interventions and maternal and child healthcare services on stunting prevalence in Indonesia based on path modeling. The study design was an ecological study, using secondary data for 2020 and 2021 from the Indonesian Health Profile published by the Ministry of Health. The total unit of analysis was 68, consisting of 34 provinces in Indonesia, and two years of analysis (resampling bootstrapping). The study used the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The result shows that maternal and child healthcare service has a significant direct effect on essential nutrition interventions of 0.786 (p-value<0.05) and indirectly has an effect on stunting with a coefficient value of -0.375 (p-value<0.05). The influence of essential nutrition intervention is directly significant on stunting with a path coefficient value of -0.477 (p-value<0.05). Integration of essential nutrition interventions and maternal and child healthcare services coverage can reduce the prevalence of stunting among children under five years old in Indonesia based on a predictive relevance value of 92.4%. Strengthening multi-sectoral convergence is necessary to tackle stunting in Indonesia.